Experimental and analytical performance evaluation of SiC power devices in the matrix converter - Safari, Saeed; Castellazzi, Alberto; Wheeler, Patrick (IEEE, 2014)
With the commercial availability of SiC power devices, their acceptance is expected grows in consideration to the excellent low switching loss, high temperature operation and high voltage rating capabilities of these devices. This paper presents the comparative performance evaluation of different SiC power devices in matrix converter at various temperatures and switching frequencies. To this end, firstly, gate or base drive circuits for Normally-off SiC JFET, SiC MOSFET and SiC BJT which taking into account the special demands for these devices are presented. Then, three 2-phase to 1-phase matrix converters are built with different SiC power devices to measure the switching waveforms and power losses for them at different temperatures and switching frequencies. Based on the measured data, three different SiC power devices are compared in terms of switching times, conduction and switching losses and efficiency at different temperatures and switching frequencies. Furthermore, a theoretical investigation of the power losses of three phase matrix converter with Normally-off SiC JFET, SiC MOSFET, SiC BJT and Si IGBT is described. The power losses estimation indicates that a 7 KW matrix converter would potentially have an efficiency of approximately 96% in high switching frequency if equipped with SiC devices.